(untitled) (Archive of Conferences, 2021)
The article deals that the modern teaching with listening skills in kindergarten. Also, it is given the easy way improving languages listening skills below. Among the other four skills, listening is the one that has been most forgotten and neglected in second language classrooms. So, teachers don’t pay much attention to this skill and teach it carelessly